2018
DOI: 10.1021/acs.langmuir.7b04106
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence Dynamics of Mobile and Immobile Fluid Interfaces

Abstract: Coalescence dynamics between deformable bubbles and droplets can be dramatically affected by the mobility of the interfaces with fully tangentially mobile bubble-liquid or droplet-liquid interfaces expected to accelerate the coalescence by orders of magnitude. However, there is a lack of systematic experimental investigations that quantify this effect. By using high speed camera imaging we examine the free rise and coalescence of small air-bubbles (100 to 1300 μm in diameter) with a liquid interface. A perfluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 50 publications
7
54
0
Order By: Relevance
“…Although the above qualitative explanation of stronger bounces from mobile surfaces is sound, predicting such a phenomenon may perhaps be counterintuitive to the expectation that two mobilesurface droplets or bubbles would coalesce much faster compared to immobile surfaces because of the much lower hydrodynamic resistance in the thin liquid film separating bubbles before the final coalescence occurs. Two mobile surfaces of droplets or bubbles, which coalesce without bouncing back, will produce a much faster coalescence, as shown in prior experiments using higher-viscosity liquids (17)(18)(19). The faster coalescence for mobile surfaces was also confirmed by the present experiments, if there is no rebound.…”
Section: Coalescence Time Scale For Mobile and Immobile Interfacessupporting
confidence: 88%
See 1 more Smart Citation
“…Although the above qualitative explanation of stronger bounces from mobile surfaces is sound, predicting such a phenomenon may perhaps be counterintuitive to the expectation that two mobilesurface droplets or bubbles would coalesce much faster compared to immobile surfaces because of the much lower hydrodynamic resistance in the thin liquid film separating bubbles before the final coalescence occurs. Two mobile surfaces of droplets or bubbles, which coalesce without bouncing back, will produce a much faster coalescence, as shown in prior experiments using higher-viscosity liquids (17)(18)(19). The faster coalescence for mobile surfaces was also confirmed by the present experiments, if there is no rebound.…”
Section: Coalescence Time Scale For Mobile and Immobile Interfacessupporting
confidence: 88%
“…One approach to demonstrate viscosity ratio effects on interface mobility and coalescence has been to use polymer droplets in immiscible polymer fluids, where both have viscosities three to five orders of magnitude higher than water (17,18). Recently, we have conducted a study (19) in which we use a perfluorocarbon liquid, PP11 [perfluoroperhydrophenanthrene (C 14 F 24 ); F2 Chemicals], that has a viscosity about 20 times higher than water to evaluate the effects of the surface mobility. There, we study the free rise of gas bubbles with mobile surfaces or water droplets with immobile surfaces and their collision with a liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…For small bubbles and low shear stress close to the Stokes regime even a trace amount of surfactant that does not change the surface tension will fully immobilize the interface and the bubbles behave like rigid particles. [38][39][40][41][42][43][44] For larger deformable bubbles their rise velocity is in agreement with the mobile-surface rise velocity predicted by the Moor theory 45 of stress-free interface bubbles, unless a higher concentration of surfactant is added. [46][47][48] Finally for the larger foam bubbles and higher shear rates, as well as in our falling cavity experiments, even for concentrations of synthetic surfactants above the CMC the interface remains free-slip.…”
Section: Paper Soft Mattersupporting
confidence: 83%
“…However this result is in good agreement with the foam rheology investigations that indicate free-slip on bubbles for foams formed using lowsurface-modulus surfactants. [34][35][36] At the same time it is in sharp contrast with the behaviour of micron sizes bubbles in water, in which case even trace amounts of contamination are found to immobilise the interface as evaluated in rising bubble terminal velocity experiments [38][39][40][41] and in bubble interaction in atomic force microscopy (AFM) experiments. 42,43 This behaviour clearly demonstrates that the mobility of the air-water interface strongly depends on the flow regime and related tangential stress applied on the bubbles or cavity interface.…”
Section: Paper Soft Mattermentioning
confidence: 99%
“…A detailed review on coalescence processes considering these effects is offered by Chesters [25] and, more recently, by Vakarelski et al [162] and Chan et al, [163] although their approach is fluid-mechanics-based and the set of equations become more complex to solve. The case for constant approach velocity (with both mobile and immobile interfaces) has been investigated by Klaseboer et al [164] For gas-liquid systems, a recent investigation by Guo et al [165] showed that decreasing both liquid density and its surface tension lead to a hampering of the coalescence process.…”
Section: Coalescencementioning
confidence: 99%